Foraminifera from Department of Lima - Verano M., Raúl (1974)
This paper gives o descriptions of six genera and seven species of foraminifera, which were found in 80 samples of sand collected 010n9 the shore of Department of Lima. AII of them represent new records for the peruvion coast.